(untitled) (Религиски дијалог и соработка, 2025)
Following the collapse of the concrete canopy at the newly reconstructed train station in Novi Sad, which killed sixteen people, Serbia has been witnessing the largest student movement in Europe since 1968. Students of diverse ideological, political, and religious backgrounds have come together to demand justice and accountability from a corrupt political establishment. This paper will strive to explore the religious and quasi-religious elements of the movement – rituals of silence, pilgrimage, ascetic endurance, and communal feasting – interpreted through a functional and anthropological approach to religion inspired by Durkheim. The study combines qualitative media discourse analysis of secular and religious communications (November 2024 to June 2025) with the author’s direct anthropological observation of protest events. This dual perspective enables an examination of how collective rituals and moral symbols emerged both in representation and in practice. The protests drew strong reactions from Serbian Orthodox Church dignitaries and other public voices, which will be examined through critical discourse analysis, focusing on how churchstate relations and religious or ideological divisions were framed. The question of various collective subjects fulfilling the usual societal functions of religion will be posed.